Experiences of Maternity Healthcare Professionals Returning to Work Following a Personal Perinatal Loss: A Scoping Review of the Literature. (February 2023) - Musodza, Wimbayi; Sheehan, Athena; Nicholls, Daniel; Dahlen, Hannah
Background: In Australia, midwives care closely for women during pregnancy and birth and the immediate postnatal period. This scoping review aimed to explore the experiences of female maternity healthcare professionals when they return to work following a personal pregnancy loss or neonatal death. Methodology: A scoping review was carried out on published and unpublished research and grey literature looking at how maternity healthcare professionals who have had a personal perinatal loss experience working in a maternity setting following the loss. A search of the literature was performed between October and December 2018, with no set limitations. A search for relevant references from included papers was also carried out. The literature was analysed thematically. The types of perinatal loss were defined as per Australian guidelines. Results: 10 articles were included in this scoping review. Four themes emerged from the literature and these were: 1) Impact of being asked, "have you got children?"; 2) Impact on professional practice; 3) Impact of pre-existing professional knowledge; 4) Importance of collegial support on return to work. Conclusions: Return to work in a maternity setting following a personal perinatal loss is emotionally challenging and requires a range of supports. Further research is needed in this area.